Atypical chronic myeloid leukaemia – a rare subtype of myelodysplastic/myeloproliferative neoplasm - Drozd-Sokołowska, Joanna E.; Waszczuk-Gajda, Anna; Mądry, Krzysztof; Dwilewicz-Trojaczek, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2018)
Atypical chronic myeloid leukaemia (aCML) belongs to the group of myelodysplastic/myeloproliferative neoplasms. Changing diagnostic criteria and the rarity of the disease, with incidence approximately 100-times lower than the incidence of BCR-ABL1 -positive chronic myeloid leukaemia, result in limited knowledge on aCML. At present the diagnosis is made based on the presence of granulocytic lineage dysplasia and precisely defined quantitative peripheral blood criteria, after exclusion of other molecularly defined myeloid neoplasms. Distinctive cytogenetic and molecular changes for aCML are missing, although recently SETBP1 mutations were described in a significant proportion of patients. The majority of patients are male and elderly. The prognosis of aCML patients is very bad, with median overall survival ranging between 10.8 and 25 months, and acute myeloid leukaemia-free survival amounting to approximately 11 months. No treatment recommendations can be made based upon current evidence, although allogeneic haematopoietic stem cell transplantation seems to be able to induce long-term remission in eligible patients.